Ultracompact Lens‐Less "Spectrometer in Fiber" Based on Chirped Filament‐Array Gratings. Issue 2 (19th October 2020) - Rahnama, Abdullah; Mahmoud Aghdami, Keivan; Kim, Young Hwan; Herman, Peter R.
Abstract : Femtosecond laser irradiation is applied to a single‐mode optical fiber to embed a filament array through the silica cladding and guiding core and form chirped Bragg gratings. Unlike a planar‐shaped refractive index modification, the long and uniform filament facilitates efficient optical scattering into azimuthally narrowed radiation modes, external and transverse to the fiber cladding. Chirping of the grating period further provides spectral focusing. The combined spectral and azimuthal focusing permits lens‐less recording of bright and high‐resolution spectra spanning across most of the visible band with a low‐cost charged coupled device camera. The flexible point‐by‐point writing enables fiber tapping of light with engineered spectral and geometric focusing properties, permitting the design of new compact photonic devices based on the all‐fiber spectrometer. Abstract : A chirped‐array of filament tracks is formed in the single‐mode fiber with femtosecond laser pulses to enable spectral focusing and radiative emission into narrow azimuthal zones outside of the cladding by first‐order Bragg response. This filament geometry provides lens‐less focusing, defining a compact all‐fiber spectrometer with a moderately high 0.3 nm resolution for light spanning fully across the visible spectrum.